2018
DOI: 10.4103/ijem.ijem_65_18
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of clinicopathological characteristics and short-term outcome of papillary thyroid carcinoma with tall cell histology and classic papillary thyroid carcinoma: A single-institution experience

Abstract: Context:Papillary thyroid carcinoma with tall cell histology (PTC-TCH) is an aggressive subtype in terms of clinicopathological features and outcome. Even 10% of tall cells can show aggressive features.Aims:The aim of this study is to investigate the behavior of PTC-TCH, to compare with classic PTC (cPTC), and evaluate the short-term outcome.Settings and Design:This is a retrospective analysis of patients with cPTC and those with TCH (PTC-TCH) seen from January 2010 to May 2017 seen in our Thyroid Cancer Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…After carefully reading full texts of these studies, we excluded 29 studies. Finally, nine studies comprising 3552 classical PTCs, 325 PTC-TCFs and 403 TCVPTCs were included for final analysis ( 5 , 6 , 7 , 9 , 13 , 14 , 15 , 16 , 17 ) ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After carefully reading full texts of these studies, we excluded 29 studies. Finally, nine studies comprising 3552 classical PTCs, 325 PTC-TCFs and 403 TCVPTCs were included for final analysis ( 5 , 6 , 7 , 9 , 13 , 14 , 15 , 16 , 17 ) ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, the thresholds of TCs for PTC-TCF were inconsistent: two studies selected the cut-off of 30–50% ( 7 , 13 ) and the remaining five studies used the threshold of 10–50% to define PTC-TCF ( 5 , 6 , 9 , 14 , 17 ). The main characteristics of included studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%